CINV1 and CINV2 are required for increased tolerance to diverse stresses after ethylene-pretreatment of germinating seeds - Esha Dutta; Mansi Patel; Colton Goodman; Allison L. Smith; Daniel M. Roberts; Brad M. Binder (PLoS ONE, 2025)
Increasing plant vigor is a major challenge because land plants are vulnerable to many stresses which impacts their survival and reduces crop production. Here, we demonstrate that pretreatment of germinating Arabidopsis thaliana seeds with ethylene in darkness followed by transition to light leads to increased stress tolerance to a variety of stresses including high heat, high salt, heavy metal, re-oxygenation after hypoxia, cold, and flagellin 22 peptide. Under the conditions used, survival without ethylene pretreatment ranged from approximately 5% to 50% depending on the stressor. After ethylene pretreatment, survival ranged from 80% to 100% under the conditions studied. Only one stress examined, freezing, was unaffected by ethylene pretreatment. Ethylene pretreatment led to increases in sucrose, fructose, and glucose prior to stress; the levels of glucose after heat stress remained high. Additionally, ethylene pretreatment prevented reactive oxygen species (ROS) accumulation in leaves after high heat stress. Two cytosolic invertases, CINV1 and CINV2, were required for ethylene-mediated increases in survival and sugar levels. In contrast to wild-type seedlings, ethylene pretreatment did not prevent ROS accumulation after high heat stress in cinv1;cinv2 double mutants. This suggests that normal breakdown of sucrose is required for these responses after pretreatment with ethylene.